Metadata specialists in transition: from MARC cataloging to linked data and BIBFRAME (data deluge column). Issue 4 (6th June 2016) - Frederick, Donna E.
Abstract : Purpose: The Association of Library Collections and Technical Services, better known as ALCTS, is a division of the American Library Association. Design/methodology/approach: Approximately once a month, ALCTS hosts an "eForum", which is a moderated email-based discussion. The February 2016 ALCTS eForum was called "Career Progression in Cataloging and Metadata". Findings: It was led by Lisa Robinson of Michigan State University and Stacie Traill of the University of Minnesota. Lisa and Stacie have provided a summary of the discussion on a publicly accessible website which is referenced at the end of the column. Originality/value: There were a number of comments and discussion threads which reflect the changing nature of library data or metadata; how it is created and managed; and the specific skill sets of catalogers and metadata librarians. This installment of the Data Deluge contains an examination and discussion of challenges associated with the role and career progression of catalogers and metadata specialists as they establish their place in the emerging linked data movement in libraries.